Preparation method of hydrophobic wood film and solution regeneration method of hydrophobic wood film

By chemically treating basswood and hydrophobic modification, an efficient hydrophobic wood membrane was prepared, which solved the problems of high cost, low flux, poor hydrophobic performance and serious temperature polarization in traditional membrane distillation and regeneration systems, and achieved efficient and corrosion-resistant solution regeneration effect.

CN119857382APending Publication Date: 2025-04-22NANJING TECH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510244642.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Traditional membrane distillation solution regeneration systems have problems such as high cost of membrane materials, low membrane flux, poor hydrophobic performance, and serious temperature polarization, resulting in low regeneration efficiency and high corrosion risk.

Method used

By performing a series of chemical treatments on natural basswood, lignin is removed and porous structure is retained, and hydrophobic modification is carried out in combination with silane coupling agent to prepare a hydrophobic wood film with high hydrophobicity, thermal anisotropy, excellent mechanical strength and corrosion resistance.

Benefits of technology

The film flux is improved, the temperature polarization phenomenon is significantly weakened, the hydrophobic properties and corrosion resistance of the film are enhanced, thereby improving the solution regeneration efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857382A_ABST
    Figure CN119857382A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrophobic wood film and a solution regeneration method of the hydrophobic wood film, and belongs to the technical field of solution dehumidification air conditioners, and the hydrophobic wood film is a film with high hydrophobicity, high porosity, low heat conductivity coefficient, good mechanical strength and high corrosion resistance. The preparation method comprises the steps that firstly, wood is pretreated in an ultrasonic cleaning instrument; then lignin is removed through a mixed solution of sodium sulfite and sodium hydroxide, so that a porous skeleton structure mainly composed of cellulose is left; then a silane coupling agent FAS (C16H19F17O3Si) is adopted for hydrophobic modification, after modification, not only can hydrophilic groups be removed, but also a micro-nano structure on the surface of the wood can be modified, and the surface of the wood film has high hydrophobicity; the contact angle of the hydrophobic wood film is not less than 140 degrees, the porosity is 0.75, the average pore size is 4.32 microns, and the average heat conductivity coefficient in the solution flowing direction is more than three times of the average heat conductivity coefficient in the direction perpendicular to the surface of the film. The characteristic of heat conduction anisotropy plays an important role in the regeneration process of a membrane distillation solution, heat of the solution is mainly transmitted in the flowing direction, meanwhile, heat transmission in the direction perpendicular to the surface of the membrane is reduced, and the temperature polarization phenomenon can be weakened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solution dehumidification air conditioning, and in particular relates to a preparation method of a hydrophobic wood film and a solution regeneration method. Background Art

[0002] Liquid dehumidification air conditioning has attracted much attention in recent years due to its advantages such as energy saving and environmental protection. In liquid dehumidification air conditioning systems, the solution regeneration process consumes the most energy. This is because the concentration of the dehumidification solution will be diluted after absorbing water, and it needs to be regenerated and concentrated. In recent years, many scholars have studied methods to improve regeneration performance and energy efficiency. However, traditional direct contact liquid dehumidification systems have defects such as low regeneration efficiency and corrosion caused by droplet carryover. Therefore, it is necessary to find an efficient and non-corrosive regeneration method.

[0003] Membrane distillation technology has been widely used in the fields of seawater desalination and industrial water treatment due to its advantages such as low operating energy consumption and indirect contact. In the regeneration of membrane distillation solution, the membrane is a crucial part, and the performance parameters of the membrane have a great influence on the performance indicators of membrane distillation regeneration. At present, there are also some urgent problems to be solved in the regeneration of membrane distillation solution, such as high cost of membrane materials, low membrane flux, poor hydrophobicity, and serious temperature polarization. Therefore, it is urgent to find a new membrane material with the above characteristics.

[0004] In response to these problems, it was found that natural wood can obtain a porous skeleton structure after specific physical and chemical treatment. This structure is very consistent with the requirements of membrane materials required for membrane distillation. Therefore, this patent prepares a hydrophobic wood membrane material that can simultaneously have high hydrophobicity, high porosity, anisotropy of thermal conductivity, excellent mechanical strength and excellent corrosion resistance, which is conducive to improving the efficiency of membrane solution regeneration and solving the problems of low efficiency of traditional solution regeneration process and corrosion caused by droplet carryover. Summary of the invention

[0005] Purpose of the invention: In the regeneration of membrane distillation solution, the membrane is a crucial part. The performance parameters of the membrane have a great influence on the membrane distillation regeneration performance indicators. Traditional organic polymer membrane materials have problems such as decreased membrane flux, membrane surface contamination, and decreased mechanical properties of the membrane after running for a period of time. The purpose of the present invention is to provide a new type of hydrophobic wood membrane with high hydrophobicity, high porosity, low thermal conductivity, good mechanical strength and strong corrosion resistance.

[0006] Technical solution: In order to achieve the above-mentioned invention object, the present invention adopts the following technical solution:

[0007] The method for preparing a hydrophobic wood film comprises the following steps:

[0008] (i) Pre-treat the basswood wood samples by washing them with deionized water in an ultrasonic cleaner for 0.5 h (ultrasonic temperature is 25°C). After washing, dry the samples in a drying oven at 65°C for 3 h for later use.

[0009] (ii) preparing a mixed solution of NaOH and Na2SO3 to obtain a lignin removal solution, wherein the concentration of NaOH is 2.5 mol / L (i.e., 100 g / L), and the concentration of Na2SO3 is 0.4 mol / L (i.e., 50.4 g / L); uniformly mixing anhydrous ethanol, FAS (perfluorododecyltriethoxysilane) and deionized water in a mass ratio of 95:2:3 to prepare a hydrophobic modified solution, and adjusting its pH value to 5.0 with acetic acid, and then slowly stirring the hydrophobic modified solution at room temperature for 4 hours to facilitate its hydrolysis.

[0010] (III) The pretreated wood sample was placed in a beaker containing lignin removal solution, heated in a water bath at 95°C for 12 hours, and then rinsed with hot distilled water to remove the residual NaOH and Na2SO3 solution. After this step, most of the lignin in the wood sample was removed.

[0011] (iv) Soak the treated wood sample in a 3% H2O2 solution at 70°C for bleaching. After the color of the sample becomes lighter, take out the sample and rinse it with cold distilled water to remove some of the residual H2O2 solution. This step removes some lignin again while bleaching the wood sample.

[0012] (V) freeze-drying the bleached wood sample for more than 12 hours to retain the porous structure of the wood sample after removing part of the lignin.

[0013] (vi) Place the freeze-dried wood sample in the FAS hydrophobic modification solution and slowly stir for more than 4 hours to ensure that the wood sample is in full contact with the hydrophobic modification solution.

[0014] (VII) The sample treated with the FAS hydrophobic modification solution was placed in a vacuum drying oven at 120° C. for 4 h, and a hydrophobic wood film was obtained after drying.

[0015] The above-mentioned method for preparing the hydrophobic wood film, the step (iii) includes the following specific contents:

[0016] Place the wood sample treated in step (i) in a beaker containing lignin removal solution, and place the beaker in a 95°C water bath for water bath heating. After heating for 12 hours, take out the sample and then rinse the sample three times with hot distilled water to remove the residual NaOH and Na2SO3 solution. When heating in a water bath, add water to the water bath in a timely manner to prevent evaporation of water, which will cause the water level in the water bath to be lower than the solution level in the beaker in the water bath. After this step, most of the lignin in the sample is removed.

[0017] In the above-mentioned method for preparing the hydrophobic wood film, the step (V) includes the following specific contents:

[0018] The sample treated in step (iv) is freeze-dried to retain the porous structure left after removing part of the lignin from the wood sample. The wood sample must be pre-frozen before freeze-drying, and the pre-freezing must freeze the wood sample to below -30°C for more than 4 hours. After pre-freezing, freeze drying is carried out, and the freeze drying time must be maintained for more than 12 hours. During the freeze drying process, when the sample temperature returns to room temperature, the freeze dryer continues to work for 2 hours before the freeze drying process ends, and the wood sample is taken out for use.

[0019] The method for regenerating a solution using the hydrophobic wood membrane comprises the following steps:

[0020] (1) Prepare a LiCl solution of corresponding concentration, transfer the prepared LiCl solution to a beaker, then place the heater, temperature controller, and micro water pump (high temperature resistant type) into the beaker, and then connect the solution pipeline system to the micro water pump. After the connection is completed, use rubber and plastic insulation cotton to completely surround the beaker and solution pipeline to reduce the heat loss of the experimental system.

[0021] (2) Start the heater and gradually heat the solution in the beaker to the corresponding experimental operating temperature. When the temperature of the LiCl solution reaches the experimental operating temperature, the temperature controller will interrupt the power supply to the heater. When the temperature drops, the temperature controller will resume the power supply to the heater, thereby controlling the automatic start and stop of the heater, thereby maintaining the relatively constant temperature of the solution.

[0022] (3) When the solution temperature reaches the set temperature of the experimental condition, turn on the power of the micro water pump, and the solution begins to circulate in the system pipeline. The flow rate of the solution is controlled by adjusting the power of the micro water pump. After observing that there is no abnormality in the circulation of the system solution, turn on the small air fan on the air side and turn on the data acquisition instrument. During the experiment, the solution temperature at the inlet and outlet of the membrane module, the air temperature on the permeate side, and the relative humidity are all transmitted to the computer through the temperature sensor, humidity sensor, and data acquisition instrument.

[0023] (4) Observe the experimental data displayed on the computer, and start recording the experimental data when the experimental data reaches a relatively stable state. The recording time for each set of experiments is 30 minutes. During the experiment, you need to pay attention to the fluctuations of the temperature of the inlet and outlet of the solution and the solution flow rate. If the fluctuation is too large, you need to adjust it to the experimental working condition value in time.

[0024] (5) After the experiment, export the experimental data and turn off the power of each instrument. When the solution temperature drops to room temperature, remove the heater, temperature controller and micro water pump in the beaker, and use deionized water to clean the solution pipeline and each instrument that has come into contact with the solution.

[0025] Advantages of the present invention:

[0026] (1) Wood resources are very abundant in nature and are renewable resources. Through a series of chemical treatment methods, most of the lignin and hemicellulose in the wood are accurately removed, retaining the wood skeleton mainly composed of cellulose, and this structure has the characteristics of thermal anisotropy and high porosity. Then, a silane coupling agent is used to hydrophobically modify the wood surface, giving it excellent hydrophobic properties. Subsequently, freeze-drying technology is used to stabilize the internal structure of the wood film and complete the overall drying, and finally a wood film with excellent hydrophobicity is obtained. At the same time, natural basswood has strong mechanical strength and corrosion resistance, which also meets the conditions of an ideal membrane material. The silane coupling agent FAS (C 16 H 19 F 17 O3Si) is hydrophobically modified, which not only removes the hydrophilic groups but also modifies the micro-nanostructure of the wood surface, making the surface of the wood membrane highly hydrophobic, thus meeting the requirements of membrane distillation regeneration.

[0027] (ii) The wood film exhibits significant anisotropy in thermal conductivity, and the average thermal conductivity along the flow direction of the solution is more than three times the average thermal conductivity in the direction perpendicular to the membrane surface. The characteristic of thermal anisotropy plays an important role in the regeneration process of membrane distillation solution. It allows the heat of the solution to be transferred mainly along the flow direction, while reducing the heat transfer in the direction perpendicular to the membrane surface, which helps to weaken the temperature polarization phenomenon. The innovative application of thermally conductive anisotropic membrane materials in the field of membrane distillation has significantly slowed down the temperature polarization effect and provided a new idea for further improving the efficiency of membrane distillation.

[0028] Beneficial effects: Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. Improve membrane flux. The membrane flux of the hydrophobic wood membrane prepared in this paper is significantly improved, and with the increase of the solution inlet temperature, the membrane flux of the wood membrane is more and more obvious compared with the literature value. When the solution inlet temperature is 80℃, the membrane flux is increased by 15.85%, and the difference between the two is 5.3kg / (m 2 h).

[0030] 2. Anisotropic thermal conductivity. The hydrophobic wood film prepared by the present invention is significantly better than the commercial film; the wood film exhibits significant anisotropic characteristics in thermal conductivity. Specifically, the average thermal conductivity in the direction perpendicular to the film surface is 0.184W / (m·K), while the average thermal conductivity along the solution flow direction is 0.596W / (m·K), which is 3.24 times the former.

[0031] 3. Weaken the temperature polarization phenomenon. The existence of thermal conductivity anisotropy of wood film makes the heat of the solution transfer more along the flow direction, so the temperature reduction of the solution is relatively small, thereby suppressing the temperature polarization phenomenon. And the temperature polarization coefficient will increase with the increase of the degree of thermal conductivity anisotropy of wood film, which further confirms that the thermal conductivity anisotropy of the wood film prepared in this paper plays a positive role in improving the temperature polarization phenomenon. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 : System diagram of wood membrane distillation solution regeneration device;

[0033] Figure 1 The medium membrane distillation regeneration system is roughly composed of four parts: solution circulation loop, wooden membrane assembly, air side pipeline and information acquisition module. The solution circulation loop mainly includes heater 1, temperature controller 2, beaker 3, micro water pump 4, solution pipeline system and external insulation material; wooden membrane assembly 5 is composed of acrylic shell and wooden membrane; air side pipeline mainly includes micro fan 6 and acrylic air duct pipeline; information acquisition module includes electronic balance 7, temperature sensor 2, humidity sensor 8, anemometer 9, flow meter 10, data acquisition instrument 11, computer 12, etc.

[0034] Figure 2 and Figure 3 : Schematic diagram of wood film and flow direction;

[0035] Figure 2 and Figure 3 The effective contact area of ​​the wood film is 9 cm 2 The cross-sectional area of ​​the flow channel on the solution side and the air side is also 9 cm 2 The two fluids adopt cross flow, the feed solution flows over the upper surface of the wood membrane, and the permeate side air blows over the lower surface of the wood membrane. Figure 2 The flow direction of the solution is perpendicular to the growth direction of the wood membrane fibers. Figure 3 The flow direction of the solution is consistent with the growth direction of the wood membrane fibers. DETAILED DESCRIPTION

[0036] The present invention firstly uses a series of chemical treatment methods to accurately remove most of the lignin and hemicellulose in the wood, and retains the wood skeleton mainly composed of cellulose. There are many hydroxyl groups on the surface of wood, which are extremely hydrophilic groups, so they need to be hydrophobicized. In nature, the surface of lotus leaves is super hydrophobic. Related studies have shown that this is because the surface of lotus leaves has low surface energy chemical components and micro-nano structures. Inspired by this, the silane coupling agent FAS (C 16 H 19 F 17 O3Si) was used for hydrophobic modification, which not only removed the hydrophilic groups but also modified the micro-nanostructure of the wood surface, making the wood film surface highly hydrophobic, thus meeting the requirements of membrane distillation regeneration. Then, a silane coupling agent was used to hydrophobically modify the wood surface, giving it excellent hydrophobic properties. Subsequently, freeze-drying technology was used to stabilize the internal structure of the wood film and complete the overall drying, and finally a wood film with excellent hydrophobicity was obtained.

[0037] Example 1

[0038] (i) Pre-treat the basswood sample by cleaning it with deionized water in an ultrasonic cleaner for 0.5 h (ultrasonic temperature is 25°C). After cleaning, dry the sample in a drying oven at 65°C for 3 h for later use.

[0039] (ii) preparing a mixed solution of NaOH and Na2SO3 to obtain a lignin removal solution, wherein the concentration of NaOH is 2.5 mol / L (i.e., 100 g / L), and the concentration of Na2SO3 is 0.4 mol / L (i.e., 50.4 g / L); uniformly mixing anhydrous ethanol, FAS (perfluorododecyltriethoxysilane) and deionized water in a mass ratio of 95:2:3 to prepare a hydrophobic modified solution, and adjusting its pH value to 5.0 with acetic acid, and then slowly stirring the hydrophobic modified solution at room temperature for 4 hours to facilitate its hydrolysis.

[0040] (III) Place the pretreated basswood sample in a beaker containing the lignin removal solution, and place the beaker in a 95°C water bath for water bath heating. Take out the sample after heating for 12 hours, and then rinse the basswood sample three times with hot distilled water to remove the residual NaOH and Na2SO3 solution. When heating in a water bath, add water to the water bath in a timely manner to prevent the evaporation of water, which will cause the water level in the water bath to be lower than the solution level in the beaker in the water bath. After this step, most of the lignin in the basswood sample is removed.

[0041] (iv) Soak the treated basswood sample in a 3% H2O2 solution at 70°C for bleaching. After the color of the sample becomes lighter, take out the sample and rinse it with cold distilled water to remove some of the residual H2O2 solution. This step removes some lignin again while bleaching the wood sample.

[0042] (V) Freeze-dry the sample after being treated with H2O2 solution to retain the porous structure left after removing part of the lignin from the wood sample. The wood sample must be pre-frozen before freeze-drying, and the pre-freezing must freeze the wood sample to below -30°C for more than 4 hours. After pre-freezing, freeze drying is carried out, and the freeze drying time must be maintained for more than 12 hours. During the freeze drying process, when the sample temperature returns to room temperature, the freeze dryer continues to work for 2 hours before the freeze drying process ends, and the wood sample is taken out for use.

[0043] (VI) Place the freeze-dried basswood sample in the FAS hydrophobic modification solution and slowly stir for more than 4 hours to ensure that the wood sample is in full contact with the hydrophobic modification solution.

[0044] (VII) The sample treated with the FAS hydrophobic modification solution was placed in a vacuum drying oven at 120° C. for 4 h, and a hydrophobic wood film was obtained after drying.

[0045] The method for regenerating a solution using the hydrophobic wood membrane comprises the following steps:

[0046] (1) Prepare a LiCl solution of corresponding concentration, transfer the prepared LiCl solution into the beaker 3, then place the heater 1, the temperature controller 2, and the micro water pump (high temperature resistant type) 4 into the beaker, and then connect the solution pipeline system to the micro water pump 4. After the connection is completed, the beaker 3 and the solution pipeline are completely surrounded by rubber and plastic insulation cotton to reduce the heat loss of the experimental system.

[0047] (2) Start the heater 1 and gradually heat the solution in the beaker 3 to the corresponding experimental operating temperature. When the temperature of the LiCl solution reaches the experimental operating temperature, the temperature controller 2 will interrupt the power supply to the heater 1. When the temperature drops, the temperature controller 2 will resume the power supply to the heater 1, thereby controlling the automatic start and stop of the heater 1, thereby maintaining the relatively constant temperature of the solution.

[0048] (3) When the solution temperature reaches the set temperature of the experimental condition, the power of the micro water pump 4 is turned on, and the solution begins to circulate in the system pipeline. The flow rate of the solution is controlled by adjusting the power of the micro water pump 4. After observing that there is no abnormality in the system solution circulation, the small air fan 6 is turned on and the data acquisition instrument 11 is turned on. During the experiment, the solution temperature at the inlet and outlet of the membrane assembly 5, the air temperature on the permeate side, and the relative humidity are all transmitted to the computer 12 through the temperature sensor 2, the humidity sensor 8, and the data acquisition instrument 11.

[0049] (4) Observe the experimental data displayed in the computer 12, and start recording the experimental data when the experimental data reaches a relatively stable state. The recording time for each set of experiments is 30 minutes. During the experiment, it is necessary to pay attention to the fluctuations of the temperature of the solution inlet and outlet and the solution flow rate. If the fluctuation is too large, it is necessary to adjust it to the experimental working condition value in time.

[0050] (5) After the experiment is over, the experimental data is exported and the power of each instrument is turned off. When the solution temperature drops to room temperature, the heater 1, temperature controller 2 and micro water pump 4 in the beaker 3 are removed, and the solution pipeline and each instrument that has been in contact with the solution are cleaned with deionized water.

[0051] The above is only a preferred embodiment of the present invention. It should be noted that, without departing from the technical principle of the present invention, a person skilled in the art may make several improvements and modifications, which should also be considered as the protection scope of the present invention.

Claims

1. A method for preparing a hydrophobic wood film, characterized in that The steps include: (i) Pre-treat the basswood wood samples by washing them with deionized water in an ultrasonic cleaner for 0.5 h (ultrasonic temperature is 25°C). After washing, dry the samples in a drying oven at 65°C for 3 h for later use. (ii) preparing a mixed solution of NaOH and Na2SO3 to obtain a lignin removal solution, wherein the concentration of NaOH is 2.5 mol / L (i.e., 100 g / L), and the concentration of Na2SO3 is 0.4 mol / L (i.e., 50.4 g / L); uniformly mixing anhydrous ethanol, FAS (perfluorododecyltriethoxysilane) and deionized water in a mass ratio of 95:2:3 to prepare a hydrophobic modified solution, and adjusting its pH value to 5.0 with acetic acid, and then slowly stirring the hydrophobic modified solution at room temperature for 4 hours to facilitate its hydrolysis. (III) The pretreated wood sample was placed in a beaker containing lignin removal solution, heated in a water bath at 95°C for 12 hours, and then rinsed with hot distilled water to remove the residual NaOH and Na2SO3 solution. After this step, most of the lignin in the wood sample was removed. (iv) Soak the treated wood sample in a 3% H2O2 solution at 70°C for bleaching. After the color of the sample becomes lighter, take out the sample and rinse it with cold distilled water to remove some of the residual H2O2 solution. This step removes some lignin again while bleaching the wood sample. (V) freeze-drying the bleached wood sample for more than 12 hours to retain the porous structure of the wood sample after removing part of the lignin. (vi) Place the freeze-dried wood sample in the FAS hydrophobic modification solution and slowly stir for more than 4 hours to ensure that the wood sample is in full contact with the hydrophobic modification solution. (VII) The sample treated with the FAS hydrophobic modification solution was placed in a vacuum drying oven at 120°C for 4 hours, and a hydrophobic wood film was obtained after drying. The hydrophobic wood film had a contact angle of not less than 140°, a porosity of 0.75, an average pore size of 4.32 μm, an average thermal conductivity in the direction perpendicular to the film surface of 0.184 W / (m·K), and an average thermal conductivity along the solution flow direction of 0.596 W / (m·K).

2. The method for preparing the hydrophobic wood film according to claim 1: characterized in that The step (three) includes the following specific contents: Place the wood sample treated in step (i) in a beaker containing lignin removal solution, and place the beaker in a 95°C water bath for water bath heating. After heating for 12 hours, take out the sample and then rinse the sample three times with hot distilled water to remove the residual NaOH and Na2SO3 solution. When heating in a water bath, add water to the water bath in a timely manner to prevent evaporation of water, which will cause the water level in the water bath to be lower than the solution level in the beaker in the water bath. After this step, most of the lignin in the sample is removed.

3. The method for preparing a hydrophobic wood film according to claim 1, characterized in that Step (V) includes the following specific contents: The sample after the treatment in step (iv) is freeze-dried to retain the porous structure left after removing part of the lignin from the wood sample. Wood samples must be pre-frozen before freeze drying. The pre-freezing must freeze the wood samples to below -30℃ for more than 4 hours. After pre-freezing, freeze drying is carried out, and the freeze drying time must be maintained for more than 12 hours. During the freeze drying process, when the sample temperature returns to room temperature, the freeze dryer continues to work for 2 hours before the freeze drying process ends, and the wood samples are taken out for use.

4. A method for regenerating a solution using the hydrophobic wood membrane, characterized in that The steps include: (i) Prepare a LiCl solution of corresponding concentration, transfer the prepared LiCl solution to a beaker (3), then place a heater (1), a temperature controller (2), and a micro water pump (4) into the beaker, and then connect the solution pipeline system to the micro water pump (4). After the connection is completed, use rubber and plastic insulation cotton to completely surround the beaker (3) and the solution pipeline, the purpose of which is to reduce the heat loss of the experimental system. (ii) Start the heater (1) and gradually heat the solution in the beaker (3) to the corresponding experimental operating temperature. When the temperature of the LiCl solution reaches the experimental operating temperature, the temperature controller (2) interrupts the power supply to the heater (1). When the temperature drops, the temperature controller (2) resumes the power supply to the heater (1), thereby controlling the automatic start and stop of the heater (1) and maintaining the relatively constant temperature of the solution. (III) When the solution temperature reaches the set temperature of the experimental condition, the power supply of the micro water pump (4) is turned on, and the solution begins to circulate in the system pipeline. The flow rate of the solution is controlled by adjusting the power of the micro water pump (4). After observing that there is no abnormality in the circulation of the system solution, the small air fan (6) on the air side is turned on, and the data acquisition instrument (11) is turned on. During the experiment, the solution temperature at the inlet and outlet of the membrane assembly (5), the air temperature on the permeate side, and the relative humidity are all transmitted to the computer (12) through the temperature sensor (2), the humidity sensor (8) and the data acquisition instrument (11). (iv) Observe the experimental data displayed in the computer (12), and start recording the experimental data when the experimental data reaches a relatively stable state. The recording time for each set of experiments is 30 minutes. During the experiment, it is necessary to pay attention to the fluctuations of the temperature of the solution inlet and outlet and the solution flow rate. If the fluctuation is too large, it is necessary to adjust it to the experimental working condition value in time. (V) After the experiment, export the experimental data and turn off the power of each instrument. When the solution temperature drops to room temperature, take out the heater, temperature controller and micro water pump in the beaker, and use deionized water to clean the solution pipeline and each instrument that has been in contact with the solution.

5. The method for regenerating a solution using a hydrophobic wood film according to claim 4, characterized in that The direction of solution flow in the membrane distillation solution regeneration experiment is the growth direction of the wood membrane fibers.

Citation Information

Patent Citations

  • High-flux super-hydrophobic wood as well as preparation method and application thereof

    CN113499760A

  • Modified super-hydrophobic membrane based on polyvinylidene fluoride as well as preparation method and application of modified super-hydrophobic membrane

    CN115364700A

  • Hydrophilic-super-hydrophobic nano-modified wood membrane distillation membrane and preparation method thereof

    CN118594264A